The ars memorativa and ecfrasis: Technical and exhortative descriptions to construct the great theatre of memory - Koji Kuwakino (Galilæana)
The highly suggestive but also emblematic relationship between the art of memory and rhetorical ecphrasis has often been noted and investigated since the earliest studies devoted to ars memorativa. Indeed, the so-called imagines agentes require strong psychic representations capable of strongly mobilizing the passions of the memory artist, effects comparable to those that are provoked by ecphrastic descriptions (enargeia). However, there are few studies that deal in depth with loci memoriae from the perspective of ecphrasis. So this contribution aims to reconsider the relationship between the art of memory and ekphrasis through the rereading of a series of early modern mnemonic treatises focusing especially on their peculiar ways of illustrating the composition of architectural mental places, described in a clear, detailed and effective way so that readers can compose them by oneself. From such an approach I believe it is possible to thoroughly highlight the synergy of words, images and spaces. Main texts to be analyzed are chosen from mnemonic treatises that present compressed architectural mental places such as theaters, palaces, cities, gardens, including Utriusque Cosmi, Maioris scilicet et Minoris (…) by Robert Fludd, Thesaurus artificiosae memoriae by Cosma Rosselli, etc.